High‐throughput field phenotyping reveals genetic variation in photosynthetic traits in durum wheat under drought. (10th July 2021) - Zendonadi dos Santos, Nícolas; Piepho, Hans‐Peter; Condorelli, Giuseppe Emanuele; Licieri Groli, Eder; Newcomb, Maria; Ward, Richard; Tuberosa, Roberto; Maccaferri, Marco; Fiorani, Fabio; Rascher, Uwe; Muller, Onno
Abstract: Chlorophyll fluorescence (ChlF) is a powerful non‐invasive technique for probing photosynthesis. Although proposed as a method for drought tolerance screening, ChlF has not yet been fully adopted in physiological breeding, mainly due to limitations in high‐throughput field phenotyping capabilities. The light‐induced fluorescence transient (LIFT) sensor has recently been shown to reliably provide active ChlF data for rapid and remote characterisation of plant photosynthetic performance. We used the LIFT sensor to quantify photosynthesis traits across time in a large panel of durum wheat genotypes subjected to a progressive drought in replicated field trials over two growing seasons. The photosynthetic performance was measured at the canopy level by means of the operating efficiency of Photosystem II ( F q ′ / F m ′ ) and the kinetics of electron transport measured by reoxidation rates ( F r 1 ′ and F r 2 ′ ). Short‐ and long‐term changes in ChlF traits were found in response to soil water availability and due to interactions with weather fluctuations. In mild drought, F q ′ / F m ′ and F r 2 ′ were little affected, while F r 1 ′ was consistently accelerated in water‐limited compared to well‐watered plants, increasingly so with rising vapour pressure deficit. This high‐throughput approach allowed assessment of the native genetic diversity in ChlF traits while considering the diurnal dynamics of photosynthesis. Abstract : Photosynthetic performance of a large durum wheat panel under progressive drought in the field was quantified using the light‐induced fluorescence transient (LIFT) sensor for high‐throughput phenotyping. Photosynthesis traits showed high genetic variability, aiding physiological crop breeding.